Efficient tools to target DNA to Podospora anserina - Michelle Déquard-Chablat; Tan-Trung Nguyen; Véronique Contamine; Sylvie Hermann-Le Denmat; Fabienne Malagnac (Fungal Genetics Reports, 2012)
Here we report the construction of two plasmids designed to target DNA sequences to two specific loci of Podospora anserina.